2011
DOI: 10.1002/wrna.110
|View full text |Cite
|
Sign up to set email alerts
|

RNAi screening: new approaches, understandings, and organisms

Abstract: RNA interference (RNAi) leads to sequence-specific knockdown of gene function. The approach can be used in large-scale screens to interrogate function in various model organisms and an increasing number of other species. Genome-scale RNAi screens are routinely performed in cultured or primary cells or in vivo in organisms such as C. elegans. High-throughput RNAi screening is benefitting from the development of sophisticated new instrumentation and software tools for collecting and analyzing data, including hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
94
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 151 publications
(266 reference statements)
0
94
0
Order By: Relevance
“…To confirm the cell fusion phenotype and exclude the possibility of an off-target effect of RNAi (Mohr and Perrimon, 2012), we overexpressed a dominant-negative form of Dome (designated dome DN ) (Brown et al, 2001) in the larval epidermis and found that these larvae again developed large syncytia upon wounding (Fig. 1E,F).…”
Section: Introductionmentioning
confidence: 98%
“…To confirm the cell fusion phenotype and exclude the possibility of an off-target effect of RNAi (Mohr and Perrimon, 2012), we overexpressed a dominant-negative form of Dome (designated dome DN ) (Brown et al, 2001) in the larval epidermis and found that these larvae again developed large syncytia upon wounding (Fig. 1E,F).…”
Section: Introductionmentioning
confidence: 98%
“…At least some of these off-target effects are presumably mediated by the cellular microRNA-processing machinery, which mistakes transfected siRNA oligos for endogenous microRNAs, loading them onto the RNA-induced silencing complex and scanning for mRNAs with suitable binding sites. Consistent with this hypothesis, it has been observed that sequencedependent off-target effects of siRNAs are primarily controlled and initiated by the "seed" region of their sequence (nucleotide positions [2][3][4][5][6][7][8], similar to what is the case for microRNAs (6,19,20). Matches to any given seed sequence typically occur in several hundred different human transcripts, suggesting that each off-target event can potentially perturb tens or hundreds of genes simultaneously.…”
Section: Significancementioning
confidence: 78%
“…Pathogens are often fast-evolving and locked in a molecular "arms race" with their hosts; thus, their interactions with cellular genes are often host-specific and must be screened in the native host species. For systematically perturbing human genes, the most widely used method is RNA interference (RNAi), which involves the use of commercial libraries of synthetic small interfering RNA (siRNA) molecules (6). A number of pioneering RNAi screens for host factors required by human pathogens have already been conducted (7)(8)(9)(10)(11)(12)(13)(14)(15), and many other human phenotypes have been screened as well (16).…”
mentioning
confidence: 99%
“…One major challenge of using RNAi is to identify the effective short interfering RNA (siRNA) target sites of a given gene and transport it efficiently to the appropriate cell or tissue to knockdown the expression of target gene (Chen and Xie, 2012;Guzman-Villanueva et al, 2012;Mohr and Perrimon, 2012). Although several published bioinformatic prediction models (Stormo, 2006;Tilesi et al, 2009) and some fluorescencebased siRNA sequence selection systems (Luo et al, 2007;Zheng et al, 2011) have proven useful, the process to select and validate optimal siRNA sites for a given gene remains empirical and laborious.…”
Section: Introductionmentioning
confidence: 99%